4-Methoxy-N-phenylaniline - Krzymiński, Karol (International Union of Crystallography, 2008)
In the molecule of the title compound, C(13)H(13)NO, the two benzene rings are oriented at a dihedral angle of 59.9 (2)°. In the crystal structure, the benzene rings of neighbouring molecules are oriented nearly parallel or perpendicular, making dihedral angles of 2.8 (2) and 79.5 (2)°, respectively. The crystal structure is stabilized by a network of C—H⋯π and N—H⋯π interactions.